Potential Therapeutic Targets of Rehmannia Formulations on Diabetic Nephropathy: A Comparative Network Pharmacology Analysis - Chan, Kam Wa; Yu, Kam Yan; Yiu, Wai Han; Xue, Rui; Lok, Sarah Wing-yan; Li, Hongyu; Zou, Yixin; Ma, Jinyuan; Lai, Kar Neng; Tang, Sydney Chi-wai (Frontiers in Pharmacology, 2022)
Background Previous retrospective cohorts showed that Rehmannia-6 (R-6, Liu-wei-di-huang-wan) formulations were associated with significant kidney function preservation and mortality reduction among chronic kidney disease patients with diabetes. This study aimed to investigate the potential mechanism of action of common R-6 variations in a clinical protocol for diabetic nephropathy (DN) from a system pharmacology approach. Study design and methods Disease-related genes were retrieved from Genecards and OMIM by searching “Diabetic Nephropathy” and “Macroalbuminuria”. Variations of R-6 were identified from a published existing clinical practice guideline developed from expert consensus and pilot clinical service program. The chemical compound IDs of each herb were retrieved from TCM-Mesh and PubChem. Drug targets were subsequently revealed via PharmaMapper and UniProtKB. The disease gene interactions were assessed through STRING and disease-drug protein-protein interaction network was integrated and visualized by Cytoscape. Clusters of disease-drug protein-protein interaction were constructed by MCODE extension. Functional annotation of clusters was analyzed by DAVID and KEGG pathway enrichment. Differences among variations of R-6 were compared. Binding was verified by molecular docking with AutoDock. Results 358 genes related to DN were identified, forming 11 clusters which corresponded to complement and coagulation cascades and signaling pathways of adipocytokine, TNF, HIF-1 and AMPK. 5 variations of R-6 were analyzed. Common putative targets of the R-6 variations on DN included ACE, APOE, CCL2, CRP, EDN1, FN1, HGF, ICAM1, IL10, IL1B, IL6, INS, LEP, MMP9, PTGS2, SERPINE1 and TNF which are related to regulation of nitric oxide biosynthesis, lipid storage, cellular response to lipopolysaccharide, inflammatory response, NF-kappaB transcription factor activity, smooth muscle cell proliferation, blood pressure, cellular response to interleukin-1, angiogenesis, cell proliferation, peptidyl-tyrosine phosphorylation and protein kinase B signalling. TNF was identified as the seed for the most significant cluster of all R-6 variations. Targets specific to each formulation were identified. key chemical compounds of R-6 have good binding ability to the putative protein targets. Conclusion The mechanism of action of R-6 on DN is mostly related to the TNF signaling pathway as core mechanism, involving amelioration of angiogenesis, fibrosis, inflammation, disease susceptibility and oxidative stress. The putative targets identified could be validated through clinical trials.